Pengaruh Pembiayaan Dana Talangan Umroh Terhadap Minat Masyarakat Menjadi Nasabah Di PT. Sharia Multifinance Astra - Fauzia Nur Hasanah; Mutiah Khaira Sihotang (Jurnal Manajemen Akuntansi (JUMSI), 2023)
This study aims to examine and determine the effect of Umroh Bailout Fund Financing on Public Interest in Becoming Customers at PT. Sharia Multifinance Astra. Research Methods This thesis is a type of quantitative research. This study uses one independent variable and one dependent variable. The independent variable in this study is the financing of Umrah bailout funds and the dependent variable in this study is community interest. The data collection technique in this study was in the form of questionnaires distributed to 50 respondents. In analyzing the data, researchers used analysis with several steps to test the validity of the data,reability test, simple regression tests and hypothesis testing. The results of this study show that the t-count value is 4.473 >t-table 2.010, meaning that the financing variable for Umrah bailout funds affects the community to become customers at PT. Sharia Multifinance Astra.